2021
DOI: 10.3390/ma14154065
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Feedback Laser Based on Tunable Photonic Hypercrystal

Abstract: In this work, we investigate the generation of light in a distributed feedback (DFB) laser composed of periodically arranged layers of hyperbolic medium and active material forming a 1D photonic hypercrystal (PHC). The scope of our study covers the analysis of laser action in the presence of different types of dispersion that are achievable in a hyperbolic medium. Using the example of a PHC structure consisting of graphene-based hyperbolic medium, we demonstrate the possibility of controlling laser action by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In the case of the PHC with HMM based on dielectric layer thickness t ZnO = 5 nm, due to dielectric character of dispersion, all observed generation spectra are similar to behavior of a conventional DFB laser with small gain/loss- and dominant index-modulation [ 25 , 40 ]. Moreover, it can be observed that generation properties predicted with the local EMT approach are very consistent with the nonlocal response for both light polarizations, compare Figure 4 a,b and Figure 4 c,d.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…In the case of the PHC with HMM based on dielectric layer thickness t ZnO = 5 nm, due to dielectric character of dispersion, all observed generation spectra are similar to behavior of a conventional DFB laser with small gain/loss- and dominant index-modulation [ 25 , 40 ]. Moreover, it can be observed that generation properties predicted with the local EMT approach are very consistent with the nonlocal response for both light polarizations, compare Figure 4 a,b and Figure 4 c,d.…”
Section: Resultsmentioning
confidence: 75%
“…It is worth noting that the vector of field amplitudes describes all modes, i.e., backward and forward propagating waves with TE (with field components ) and TM (with field components ) polarizations, that exists in the medium. More detailed description of presented approach may be found in our previous research [ 15 , 16 , 25 ]. Finally, by assuming appropriate conditions for adjacent layers/media, it is possible to formulate a relationship between amplitudes at the input c in and output side c out of a single layer where is the transfer matrix of the layer, is the thickness of the considered layer, while is eigenvector matrix of output layer/medium.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations